Methodological approaches to the formation of harmonious interpersonal relationships of future teachers - Kharkivska, A. (Problems of Engineer-Pedagogical Education, 2021)
The article reveals the essence of the methodology of pedagogical science and the prerequisites for the study of methodological approaches to the formation of harmonious interpersonal relationships of future teachers. Methodological approaches to the problem of formation of harmonious interpersonal relations of future teachers are substantiated, which includes civilization-anthropological, culturological, system, synergetic, axiological, environmental, activity, and reflexive approaches. The characteristic of each methodological approach according to the research problem is given. The author notes that the civilizationanthropological approach to the problem of forming harmonious interpersonal relations of future teachers provides consideration of their participants as biosocial, cultural, spiritual beings who are the main landmark of the pedagogical process, able to transform based on knowledge of people's culture, traditions, national heritage, historical ontogenesis of values, beliefs, views of society. It is determined that the culturological approach to the problem of formation of harmonious interpersonal relations of future teachers promotes the formation of a culturally appropriate worldview. It is established that the system approach ensures the unity of all participants in the educational process of higher education institutions in the formation of harmonious interpersonal relationships of future teachers. The significance of the synergetic approach is revealed, which is an expansion of ideas about the reality of the pedagogical system. It is noted that according to the axiological approach the process of formation of harmonious interpersonal relations of future teachers is a dialectical integrated unity of spiritual, moral, ethical, humane, culturological, social, intellectual, emotional, and pedagogical values. It is established that the environment of a pedagogical higher education institution should become a plane for the exchange of cultural meanings between the participants of harmonious interpersonal relations. It is determined that the reflexive approach makes it possible for future teachers to identify and understand the existing causes of imbalance in real interpersonal relationships and to develop an individual strategy to restore harmony in relationships with others. It is emphasized that for the sake of integrity of research on the problem of formation of harmonious interpersonal relations of future teachers it is necessary to use the specified methodological approaches in symbiosis.